Design Potential of Technical Hemp and PLA Nonwovens - Katarzyna Zimna; May Kahoush; Marcin Barburski (Journal of Natural Fibers, 2024)
The main purpose of the article is to present the potential use of hemp fibers as reinforcement in composites, but from a design perspective. The authors ask whether sustainable nonwovens, produced based on natural fibers, have the potential as a material for designers and artists and not only as a technical textile. Technical production of nonwovens like carding, punching and laser cutting was used to achieve not just functional, but also aesthetic quality of the samples. The possibilities of utilizing natural materials for design endeavors were presented. The production process of these items was described, along with the main design concept. Research was carried out through a series of interdisciplinary activities, using the knowledge and tools typical for textile and materials engineering, as well as the methodology and strategies derived from the fields of visual art and design. It has been shown that during the development of a new sustainable material significant attention should be paid to design aspects, so it shows its full potential, as not just being eco-friendly, but also functional and aesthetic. While technical hemp and PLA composites have been produced and studied before, the design aspect is unique in the current study.